Towards selecting the optimized external wall solution in Iran: Comparison between life cycle assessment (LCA), cost benefits, and thermal performance. (September 2022) - Pakdel, Ali
Abstract: External walls, as the main components of a building's envelope, directly affect the building's thermal and environmental performance due to their high carbon emissions, life cycle costs, and user comfort. As the buildings are responsible for one-third of global GHG emissions, choosing the most effective solutions for external walls is crucial to combat the environmental crisis. This paper aims to identify and assess conventional external walls in Iran. A multi-criteria scoring system is established to evaluate them regarding carbon emissions, cost benefits, and thermal performance (R-value). A selection criteria is defined, and a total of 45 external walls are identified and categorized into three wall types: solid, filled cavity, and partial cavity walls. Assessing environmental impact involves conducting a cradle-to-handover simplified life cycle assessment. Cost assessment is performed using construction costs, and thermal performance assessment is conducted based on thermal conductivity coefficient and thickness. Based on the results, the highest scores belong to partial cavity walls. Partial cavity walls perform better than simple and filled cavity walls, although the simple wall is Iran's most widely used wall solution. The manufacturing stage represents the more significant contribution to environmental impact in all cases, followed by transportation and construction. The environmental analysis indicates that the structural layer (53.7%), followed by external finishing (14%), and transportation (12.1%) are the three highest contributors, respectively. The results also stress the importance of transport protocols in the carbon emissions reduction of external walls by indicating the structural layer as a carbon hotspot. Highlights: Life cycle assessment (LCA), cost and R-value assessment of external walls of Iran. Scoring system for a holistic evaluation of external wall solutions. Partial cavity walls, solid walls, and filled cavity walls assessment. Structure layer, exterior finishing, and transportation as carbon hotspots. Selecting low-capacity lorry than reducing the travel distance.